Knowledge Mapping of Angelica sinensis (Oliv.) Diels (Danggui) Research: A Scientometric Study - Lu, Cuncun; Liu, Ming; Shang, Wenru; Yuan, Yuan; Li, Meixuan; Deng, Xiuxiu; Li, Huijuan; Yang, Kehu (Frontiers in Pharmacology, 2020)
Background: Traditional Chinese Medicine (TCM) has been widely accepted and applied worldwide, and many publications related to Angelica sinensis (Oliv.) Diels (AS, Chinese name is “Danggui”) have been published. However, to date, there has not been a scientometric study to systematically analyze the intellectual landscape and emerging research trends regarding AS. Therefore, we performed a scientometric study to address this gap. Methods: Publications related to AS published from 2009 to 2018 were identified and selected from the Web of Science (WoS) Core Collection on May 30, 2019 using relevant keywords. HistCite, CiteSpace and Excel 2016 software tools were used to conduct this scientometric study. Results: Seven hundred and sixty-seven articles (including 717 primary articles and 60 review articles) and their cited references were included and analyzed. The majority of publications (N=565, 73.7%) were published in mainland China, with Nanjing University of Chinese Medicine contributing the most publications (N=42, 5.5%). The first core journal was Journal of Ethnopharmacology (N=58, 7.6%; impact factor=3.414). The identification and assessment of active components (like ferulic acid) of AS and their pharmacological actions (such as immunomodulatory effects) are the current research foci for AS research. Conclusions: The present scientometric study provides an overview of the development of AS research over the previous decade using quantitative and qualitative methods, and this overview can provide references for researchers focusing on AS.